A Study of the Maudhu'i Hadith on Waqf and Its Implications in Addressing Contemporary Economic Deviations - Riady, Achmad; Ahmad, Arifuddin; Aisyah, Siti (State Islamic Institute of Palopo, 2025)
Waqf holds a strategic position within the Islamic economic system due to its ability to integrate spiritual values with socio-economic functions. This study aims to examine the implementation of the thematic (maudhu’i) approach in understanding hadiths related to waqf and to evaluate their relevance in strengthening contemporary Islamic economics. This research employs a qualitative method based on a literature review with a descriptive-analytical approach. Primary data were derived from hadiths found in major collections, analyzed through thematic classification, validation of chains of narration (sanad) and content (matan), and critical analysis. The findings indicate that waqf-related hadiths can be categorized into several key themes, including waqf jurisprudence, social benefits, and productive waqf. The validity of the hadiths is supported through takhrij and sanad-matan criticism, while their correlation with Islamic economic principles is reflected in social justice, wealth redistribution, and community empowerment. Innovations such as cash waqf, waqf sukuk, and Islamic fintech have expanded the scope of waqf implementation in sustainable economic development. Government bodies and financial institutions play a strategic role in strengthening the waqf ecosystem through supportive regulations and public literacy. This study concludes that integrating hadith scholarship and Islamic economics through the thematic approach makes a significant contribution to advancing both the knowledge and practice of waqf in the contemporary era.